Compressed fuzzy logic based multi-criteria AODV routing in VANET environment - Taqwa Oday Fahad; Abduladhem A. Ali (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Vehicular ad hoc networks (VANETs) are the core of intelligent transportation systems (ITS) to obtain safety, better transportation services, and improved traffic management. Providing more reliable and efficient on demand routing protocol is one of the main challenges in these networks research scope. This paper argues a compressed fuzzy logic based method to enhance Ad hoc on demand distance vector (AODV) routing decision by jointly considering number of relays, distance factor, direction angle, and vehicles speed variance. The proposed scheme is simulated in both freeway and urban scenarios with different number of vehicles using real time interaction between both OMNet++ and SUMO simulators. Simulation results show that the proposed approach can get better performance in terms of packet delivery ratio, throughput, mean delay, and number of sent control packets.